2007
DOI: 10.1002/dvdy.21411
|View full text |Cite
|
Sign up to set email alerts
|

Genes of Hippo signaling network act unconventionally in the control of germline proliferation in Drosophila

Abstract: Hippo pathway and its related genes are required for growth control in various somatic tissues. The mutations of Hippo pathway components lead to tissue overgrowth cell-autonomously. Surprisingly, when we generated germline mutant clones of Hippo-network genes such as fat, expanded, hippo, salvador, and warts, we did not observe any overgrowth of these mutant cells. Consistently, overexpression of the progrowth gene yorkie, which is normally inhibited by Hippo signaling, did not lead to germline overgrowth eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…Clonal mis‐expression of an activated form of Yki (Yki Act (Oh & Irvine, )) resulted in CySC clones that out‐competed wild‐type CySCs and GSCs at the niche (Fig G and H, P < 0.0014). Consistent with an essential role of yki in CySCs, we found that yki was required autonomously for self‐renewal in CySCs but not in GSCs (Fig A, E and F), the latter consistent with a prior report (Sun et al , ). Finally, we addressed whether Hh and Hpo, two proliferative pathways in CySCs, were epistatic.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Clonal mis‐expression of an activated form of Yki (Yki Act (Oh & Irvine, )) resulted in CySC clones that out‐competed wild‐type CySCs and GSCs at the niche (Fig G and H, P < 0.0014). Consistent with an essential role of yki in CySCs, we found that yki was required autonomously for self‐renewal in CySCs but not in GSCs (Fig A, E and F), the latter consistent with a prior report (Sun et al , ). Finally, we addressed whether Hh and Hpo, two proliferative pathways in CySCs, were epistatic.…”
Section: Resultssupporting
confidence: 92%
“…However, careful analysis of GSC dynamics has suggested that they also undergo neutral competition, albeit at a slower loss/replacement rate than CySCs (Wallenfang et al, 2006;Sheng & Matunis, 2011;Salzmann et al, 2013). Thus, within the same stem cell niche, two markedly different strategies for selfrenewal are in use, exemplified by the requirement for yki in CySC self-renewal, but not in GSC self-renewal (this study and Sun et al, 2008). This is particularly surprising as the two stem cell populations are by necessity linked, in that they need to produce offspring in the correct ratio, as well as the fact that CySCs support GSC self-renewal through BMP production (Leatherman & Dinardo, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…This is why the fecundity of BmYki RNAi silkworm was significantly reduced (Liu et al, ). Furthermore, we noticed that the expression of BmYki in TE did not increase in later developmental stages, which is consistent with previous observations that overexpression of BmYki did not lead to spermatogonial proliferation (Sun et al, ). BmYki expression was extremely high in MG, which affects the uptake of nutrients and, indirectly, body size (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…As one of the most crucial cell signaling pathways, the Hippo signaling pathway regulates female reproductive system development [34,35,36,37,38]. We provide evidence for the expression of Hippo pathway genes in the different stage mouse ovaries and propose a novel role for Hippo signaling in regulating primordial follicle formation.…”
Section: Discussionmentioning
confidence: 86%